Risk factors associated with the development of postpartum diabetes in Japanese women with gestational diabetes - Yukari Kugishima; Ichiro Yasuhi; Hiroshi Yamashita; So Sugimi; Yasushi Umezaki; Sachie Suga; Masashi Fukuda; Nobuko Kusuda (BMC Pregnancy and Childbirth, 2018)
Abstract Background Although the onset of gestational diabetes (GDM) is known to be a significant risk factor for the future development of type 2 diabetes, this risk specifically in women with GDM diagnosed by the International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria has not yet been thoroughly investigated. This study was performed to investigate the risk factors associated with the development of postpartum diabetes in Japanese women with a history of GDM, and the effects of the differences in the previous Japanese criteria and the IADPSG criteria. Methods This retrospective cohort study included Japanese women with GDM who underwent at least one postpartum oral glucose tolerance test (OGTT) between 2003 and 2014. Cases with overt diabetes in pregnancy were excluded. We investigated the risk factors including maternal baseline and pregnancy characteristics associated with the development of postpartum diabetes. Results Among 354 women diagnosed with GDM during the study period, 306 (86%) (116/136 [85.3%] and 190/218 [87.2%] under the previous criteria and the IADPSG criteria, respectively) who underwent at least 1 follow-up OGTT were included in the study. Thirty-two women (10.1%) developed diabetes within a median follow-up period of 57 weeks (range, 6–292 weeks). Eleven (9.5%) and 21 (11.1%) were diagnosed as GDM during pregnancy based on the previous Japanese criteria and the IADPSG criteria, respectively, which did not significantly differ between those criteria. A multivariate logistic regression analysis revealed that HbA1c and 2-h plasma glucose (PG) at the time of the diagnostic OGTT during pregnancy were independent predictors of the development of diabetes after adjusting for confounders. The adjusted relative risk of HbA1c ≥5.6% for the development of diabetes was 4.67 (95% confidence interval, 1.53-16.73), while that of 2-h PG ≥183 mg/dl was 7.02 (2.51-20.72). Conclusions A modest elevation of the HbA1c and 2-h PG values at the time of the diagnosis of GDM during pregnancy are independent predictors of the development of diabetes during the postpartum period in Japanese women with a history of GDM. The diagnostic criteria did not affect the incidence of postpartum diabetes.